AN ANALYSIS OF THE THEME OF BEAUTY IN THE DRAMA PARIZAAD BY HASHIM NADEEM - Maria Khaleeq; Sahar Gul; Aiman Khaleeq (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of this study is to analyze beauty as portrayed by Hashim Nadeem in a Pakistani drama "Parizaad”. Beauty is the combination of different qualities and traits that please senses and enhance the mind and soul in a joyful and pleasurable way. Beauty is an abstract concept that contributes to physical appearance and qualities of a person. Beauty is a joy forever. To achieve that joy people usually focus on their physical appearance they want to get fitted in all beauty standards. An attempt is made to explore the theme of beauty and its effects on an individual’s life concerning the protagonist of the drama Parizaad. The data for this research is collected from the Drama Parizaad by Hashim Nadeem in the form of text. This research makes use of thematic analysis as its research methodology and is thus descriptive. The findings of the research show that people should not make it a priority to attain outer beauty. It will affect their intellect and increase insecurity. In order to fulfill the beauty standards people may become morally down and feel less competent. Moreover, sometimes it becomes difficult to get an ideal figure that’s why most people become insecure about their appearance. After analysis of the data, it was found that the life of the Protagonist of the drama was highly affected by beauty standards set by society and make him insecure about his skin complexion. In order to achieve beauty standards people usually focuses on outer beauty and did not improve their inner self. Inner beauty can make a person more peaceful. It can lead to a friendly environment. And people become less insecure. They start knowing their worth and abilities.